Impact of the Productive SafetyNet Program on the minimum acceptable diet in the rural community of South Gondar Zone, Northwest Ethiopia - Engidaw, Melaku Tadege; Gebremariam, Alemayehu Digssie; Kefale, Belayneh; Tesfa, Desalegn; Tiruneh, Sofonyas Abebaw; Shiferaw, Yalelet Fentaw (Frontiers in Sustainable Food Systems, 2023)
Background: Even though numerous factors contribute to undernutrition, it can occur quickly due to poor intake and illness. A minimum acceptable diet is one of the proxy measures for adequate consumption, which is an impact indicator for the Productive SafetyNet program (PSNP). As a result, this study aimed to assess the impact of PSNP on the minimum acceptable diet among rural children in South Gondar Zone, Northwest Ethiopia. Methods: A community-based cross-sectional study design was employed in the selected woredas of South Gondar Zone, Northwest Ethiopia, from December 1 to January 30, 2017. A total of 442 participants' data were analysed. The data were collected by asking their mother or caregiver during the study period. A multistage sampling technique was employed to select study subjects and interviews using a structured questionnaire. Stata version 16 (MP) was employed to carry out statistical analysis. A binary logistic regression model was employed to identify significant variables. The statistical significance was declared at a p-value of ≤0.05. Results: The highest proportion of adequate diet diversity scores (261(59.05%)) was from households who graduated (not part of it) from PSNPs. In this study, the magnitude of adequate dietary diversity, meal frequency, and minimum acceptable diet was 79.86%, 82.58% and 66.52%, respectively. Marital status (AOR = 3.98, 95% CI: 1.39, 11.40), child age (AOR = 2.82, 95% CI: 1.78, 4.47), educational status of the father (AOR = 0.56, 95%CI: 0.35, 0.89), wealth index (AOR = 0.27, 95% CI: 0.12, 0.64) and place of delivery (AOR = 3.14, 95% CI: 1.47, 6.73) were the significant predictors for minimum acceptable diet uptake by children. Conclusion: In this study, two-thirds of the children had/received a minimum acceptable diet. Also, children from households with productive SafetyNet users had a low minimum acceptable diet. Marital status, father's educational status, child age, wealth index and place of delivery were the associated factors to have an adequate intake of minimum acceptable diet by the children. So, efforts to address sociodemographic and child-related factors during routine care are crucial. Keywords: Impact; Productive SafetyNet Program; Minimum Acceptable diet; Children; Ethiopia